Gaya Kepemimpinan Kepala Sekolah Perempuan dalam Meningkatkan Kinerja Guru - Mustajib; Patoni , Achmad; Maunah , Binti (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
This study aims to describe the leadership style of the principal in improving teacher performance at SD Islam NU Sekaran. The methodology of this study uses a qualitative discriptive approach, the informants are the principal and teachers. Data collection techniques for interviews, observation, and documentation. Test the validity of the trigulation technique data. The results of the study are basically indicators of 8 indicators that have been implemented and there are 2 indicators that have not been implemented, as for the indicators are: providing motivation, work skills, coaching, discipline, giving consultations, awarding, conducting class visits, showing attitudes, and exemplary behavior, building active, creative work, developing teacher production. As for teacher performance, it is quite good, because of the six indicators, there are four indicators carried out optimally. The indicators are: arranging lesson plans, managing learning activities, holding interpersonal relationships, conducting assessments, following up on assessment results, mastering academic studies. Thus, it can be concluded that the principal's leadership in improving teacher performance greatly contributes to the progress of learning quality so that it can encourage the quality of education where the performance of education personnel is the key to success in the world of education